The efficacy of "High Pick and Roll" in relation to the defence`s reaction and its effect on the result of the game - Koutsouridis, C.; Karamousalidis, G.; Galazoulas, C. (International Journal of Performance Analysis in Sport, 2018)
This research was conducted to find out how effective the High Pick and Roll is, according to the defence`s reaction. This survey also investigates the total impact of this offensive strategy on the game`s final result. The sample consisted of 20 randomly selected basketball games of the Olympic Games in Rio (2016). The results show that the outcome of the High Pick and Roll can affect the result of the game (p = 0.001). Furthermore, there is an important statistical difference between the effectiveness of High Pick and Roll against various defensive plays. When the defending team played Trail and Sag, the majority of the attacks were successful whereas when the team played Switch, Deny or Trap most of attacks were missed (p = 0.01). Finally, most of attacks ending with a ball handler`s Drive were successful while when the ball handler was shooting, a great percentage of Shots were missed (p = 0.01). Apart from that, the effectiveness of each defensive play and the effectiveness of the offensive outcomes were also depicted. From the data presented above, it is clear that the High Pick and Roll is a crucial factor in basketball and the information and statistics included in this paper could be useful for basketball coaches, both from theoretical and practical perspective.